Surveillance for Streptococcus pneumoniae Meningitis in Children Aged <5 Years: Implications for Immunization in Uganda - Kisakye, Annet; Makumbi, Issa; Nansera, Denis; Lewis, Rosamund; Braka, Fiona; Wobudeya, Eric; Duku, Chaplain; Nalumansi, Esther; Mbabazi, William; Bradford, D. Gessner (Clinical Infectious Diseases, 2009)
Affordable pneumococcal conjugate vaccines will soon become available to developing countries through the Global Alliance for Vaccines and Immunization. Data on Streptococcus pneumoniae meningitis epidemiology in Uganda will assist decision makers in determining the best national vaccine policy. We reviewed acute bacterial meningitis surveillance data for children aged !5 years from 3 sentinel surveillance sites in 3 Ugandan districts collected from 2001 through 2006. Serotype and antibiotic-resistance testing were performed on pneumococcal isolates collected from 2005 through 2006 from the Kampala district in the tropical central region of Uganda. Minimum pneumococcal meningitis incidence estimates were calculated for a portion of the Kampala district and all of the Gulu district, where case ascertainment was more complete. At the 3 sites, 14,388 probable acute bacterial meningitis cases were observed. The most common cause identified was S. pneumoniae ( ; 35% of all confirmed cases), which had an overall case fatality ratio of 19%. Yearly n p 331 pneumococcal meningitis incidence was 3–20 cases per 100,000 population in Kampala versus 28–42 cases per 100,000 population in Gulu. The most commonly identified serotypes were 6A/6B (40%); 43% of isolates were serotypes that are in the available 7-valent pneumococcal conjugate vaccine and 70% are in the proposed 13- valent pneumococcal vaccine. Twenty-five isolates (83%) had intermediate resistance to penicillin but none were fully resistant. Pneumococcal meningitis is common and severe in Uganda, indicating a role for the pneumococcal conjugate vaccine.